ENVIRONMENT-BASED PHYSICAL EDUCATION: IMPLEMENTATION OF USED GOODS AS AN EDUCATIONAL GAME MEDIA FOR CHILDREN - Mado, Arifin; Wardana, Mahardika Darmawan Kusuma (Journal of Higher Education and Academic Advancement, 2025)
Objective: This research aims to develop and implement educational game media from used goods in learning environment-based physical education for early childhood. Method: The approach used is Research and Development (R&D) with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The research subjects involved 20 teachers from KB Kindergarten Aisyiyah Wonocolo Sepanjang. Result: The results of the analysis show that there is a need for teachers for physical learning media that is innovative, economical, and environmentally friendly. At the stage of development, game media from used items such as plastic bottles, cardboard, and raffia rope were validated by media experts and physical education experts with results that were very feasible to use. Media implementation is carried out through direct learning with children and evaluation is carried out through observation and questionnaires to teachers. The results show that educational game media from used goods is able to improve children's gross motor skills, motivate involvement in physical activities, and instill the value of environmental concern. Novelty: Thus, used goods-based educational game media can be an alternative to integrative and contextual physical education learning solutions for early childhood while supporting character learning and environmental awareness from an early age.